2016
DOI: 10.1021/acs.jafc.5b05191
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Binding of Heavy Metals by Black Sesame Pigment: Toward Innovative Dietary Strategies To Prevent Bioaccumulation

Abstract: Black sesame pigment (BSP) was shown to bind lead, cadmium, and mercury at pH 7.0 and to a lower extent at pH 2.0. BSP at 0.05 mg/mL removed the metals at 15 μM to a significant extent (>65% for cadmium and >90% for mercury and lead), with no changes following simulated digestion. The maximum binding capacities at pH 7.0 were 626.0 mg/g (lead), 42.2 mg/g (cadmium), and 69.3 mg/g (mercury). In the presence of essential metals, such as iron, calcium, and zinc, BSP retained high selectivity toward heavy metals. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…[3][4][5] Similarly, a group of researchers reported that hemicellulose and pectin also could bind heavy metals (Pb, Cu, and Cd) that can improve health via fiber-containing food. [6] Various researchers investigated dietary fiber in terms of its potential to scavenge heavy metals after it enters the body [7][8][9] and to elucidate the dietic factors that could affect the heavy metal-binding capacity, some endogenous factors like proteins and exogenous factors like pH. [10,11] Rice bran is an abundant, low-cost, underutilized lignocellulosic material and has usually been discarded directly or used as feed without effective utilization.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Similarly, a group of researchers reported that hemicellulose and pectin also could bind heavy metals (Pb, Cu, and Cd) that can improve health via fiber-containing food. [6] Various researchers investigated dietary fiber in terms of its potential to scavenge heavy metals after it enters the body [7][8][9] and to elucidate the dietic factors that could affect the heavy metal-binding capacity, some endogenous factors like proteins and exogenous factors like pH. [10,11] Rice bran is an abundant, low-cost, underutilized lignocellulosic material and has usually been discarded directly or used as feed without effective utilization.…”
Section: Introductionmentioning
confidence: 99%
“…The black pigment was purified by hydrolytic treatment of the seeds after removal of lipid components, but its insolubility hampered a detailed structural analysis. Solid state spectroscopy coupled to chemical degradation methodologies and model studies indicated coniferyl alcohol-derived units as the main structural components [16,17] (Figure 2). …”
Section: Main Sources Of Natural Phenol Polymersmentioning
confidence: 99%
“…A marked ability to bind metal ions, particularly toxic heavy metals, was shown for the pigment purified from black sesame seeds [17]. The beneficial effects on lipid profile of dietary supplementation with black seeds, particularly cumin, on diabetic patients were assessed by human and animal trials [150].…”
Section: Main Applications Of Phenol-based Polymers In Food and Hementioning
confidence: 99%
“…However, while there are foods which may favour human exposure to this metal, there are also foods which may reduce its toxicity. Naturally derived products capable of chelating heavy metals, in order to encourage their expulsion, are currently being used and this use is increasing [41,42]. In particular, current research has brought to light the ability of dietary fibers to perform Hg chelation during gastric-intestinal transit [43].…”
Section: Hg and Nutritionmentioning
confidence: 99%